Rear‐edge daylily populations show legacies of habitat fragmentation due to the Holocene climate warming. (23rd December 2022) - Masuda, Kazutoshi; Setoguchi, Hiroaki; Nagasawa, Koki; Ishihara, Masae Iwamoto; Sawa, Kazuhiro; Horie, Kenji; Tsuboi, Hayato; Fukumoto, Shigeru; Tango, Tsuguoki; Sakaguchi, Shota
Abstract: Aims: Quaternary climate changes dramatically affected species' distributions and thus impacted genetic diversity patterns, particularly for rear‐edge populations. Empirical studies have shown the southernmost (rear‐edge), fragmented populations of Japanese woody plants can harbour high genetic diversity owing to their origin in southern glacial refugia. The effect of Holocene climate warming on rear‐edge populations has, however, rarely been demonstrated. We assessed whether the genetic structure of populations of temperate plants in Japan can be interpreted to show legacies of both icy (Last Glacial Maximum, LGM) and warm (Holocene) climates. Location: Japanese Archipelago. Taxon: Hemerocallis middendorffii (Asphodelaceae). Methods: Population genetic profiles of 737 individuals from 41 populations were analysed to examine population structure and past population demography, using 12 EST‐SSR markers. Present and past suitable habitat areas during the LGM and the Holocene climatic optimum were estimated by ecological niche modelling (ENM). Reconstructed palaeodistribution was combined with population genetics to statistically predict population demographics in relation to past climate changes. Results: Genetic analysis of the 41 populations revealed 6 regional population groups. Four groups widely dominating the northern–central ranges harboured high genetic diversity, whereas genetic divergence within the groups was low. In contrast, the two groups at the southwestern edge were geographically and genetically isolated, and they showed the lowest genetic diversity. The estimated palaeodistributions showed a decrease in the suitable range during the Holocene in comparison with that at the LGM, and only habitat suitability in the Holocene was able to predict the genetic diversity across the range. Main conclusions: Populations at the centre of the current distribution harbour high genetic diversity because they remained stable during both cold and warm periods. However, habitat fragmentation and population decline in relation to climate warming during the Holocene resulted in genetic isolation and impoverishment of the rear‐edge populations.